2014
DOI: 10.7243/2054-9911-2-4
|View full text |Cite
|
Sign up to set email alerts
|

Restless legs syndrome and cancer: an analysis in three independent studies

Abstract: We report results from three independently conducted studies on the prevalence of cancer in restless legs syndrome (RLS) cases and non RLS cases. Already in 1955 Ekbom observed RLS in patients with subsequently detected cancer. Since then only three case reports and one article assessed the relationship between RLS and cancer patients undergoing chemotherapy. The observed proportion of RLS in these cancer patients (18.3%) was about twice as high as in general population studies. Two of our studies were general… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…There have been a few case reports of RLS as an early symptom of malignancy, including multiple myeloma, bladder cancer, and gastrointestinal cancer (Brocklehurst, 2003; EKBOM, 1955; Parish, 2005). On a larger scale, an epidemiological study in Europe found a significantly increased prevalence of cancer in patients with RLS compared to the age-matched general population (Fuhs et al, 2014). Likewise, a large cross-sectional study also reported the prevalence of RLS in cancer patients undergoing chemotherapy in Italy to be 18.3%, nearly twice greater than that of the general population (Ostacoli et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…There have been a few case reports of RLS as an early symptom of malignancy, including multiple myeloma, bladder cancer, and gastrointestinal cancer (Brocklehurst, 2003; EKBOM, 1955; Parish, 2005). On a larger scale, an epidemiological study in Europe found a significantly increased prevalence of cancer in patients with RLS compared to the age-matched general population (Fuhs et al, 2014). Likewise, a large cross-sectional study also reported the prevalence of RLS in cancer patients undergoing chemotherapy in Italy to be 18.3%, nearly twice greater than that of the general population (Ostacoli et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…[40] Similar results ranging from three to nine times the prevalence in normal population have been reported earlier as well; however, these subjects were undergoing chemotherapy and reported in solid tumors. [151631] Lesser prevalence has been reported in subjects undergoing palliative care, probably related to use of opioid therapy during palliation. [14] Anemia is common in patients suffering from cancer, as also seen in the present study [Table 2].…”
Section: Discussionmentioning
confidence: 99%
“…[15] Conversely, higher prevalence of malignancies has also been reported among patients suffering from RLS; however, it was not related to either radiotherapy or chemotherapy. [16] For unknown reasons, RLS can also be an antecedent to the diagnosis of malignancy. [16]…”
Section: Introductionmentioning
confidence: 99%